2018
DOI: 10.4103/aca.aca_168_17
|View full text |Cite
|
Sign up to set email alerts
|

Sedation effects by dexmedetomidine versus propofol in decreasing duration of mechanical ventilation after open heart surgery

Abstract: Objective:The objective of this study was to compare the suitability (efficacy and safety) of dexmedetomidine versus propofol for patients admitted to the intensive care unit (ICU) after the cardiovascular surgery for the postoperative sedation before weaning from mechanical ventilation.Background:Sedation is prescribed in patients admitted to the ICU after cardiovascular surgery to reduce the patient discomfort, ventilator asynchrony, to make mechanical ventilation tolerable, prevent accidental device removal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 12 publications
1
24
0
1
Order By: Relevance
“…In the first case, the implementation of advanced weaning techniques, such as proportional assist ventilation and the neurally adjusted ventilator assist, have been documented to reduce the length of mechanical ventilation (Lewis et al, 2019). In the second, trials regarding novel molecules (Traversa, 2019) such as Dexmedetomidine, have documented the effectiveness of a safer and lighter sedation, keeping the patient awake and capable of participating in daily care, allowing a faster extubation as compared to traditional medication (e.g., Propofol) (Elgebaly & Sabry, 2018; Moreira & Neto, 2016). In addition, international guidelines have recommended the multidisciplinary approach of the ABCDE bundle, that incorporates Awakening, Breathing, Coordination (or Choice) of sedatives, Delirium monitoring and management, and Early mobility on a daily basis, in order to obtain better outcomes such as a decreased length of in‐ICU‐stay, a reduced mechanical ventilation duration and an early physical recovery (Moraes et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the first case, the implementation of advanced weaning techniques, such as proportional assist ventilation and the neurally adjusted ventilator assist, have been documented to reduce the length of mechanical ventilation (Lewis et al, 2019). In the second, trials regarding novel molecules (Traversa, 2019) such as Dexmedetomidine, have documented the effectiveness of a safer and lighter sedation, keeping the patient awake and capable of participating in daily care, allowing a faster extubation as compared to traditional medication (e.g., Propofol) (Elgebaly & Sabry, 2018; Moreira & Neto, 2016). In addition, international guidelines have recommended the multidisciplinary approach of the ABCDE bundle, that incorporates Awakening, Breathing, Coordination (or Choice) of sedatives, Delirium monitoring and management, and Early mobility on a daily basis, in order to obtain better outcomes such as a decreased length of in‐ICU‐stay, a reduced mechanical ventilation duration and an early physical recovery (Moraes et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Dexmedetomidine (DEX) is a selective α2‐adrenergic agonist widely used as a sedative in clinical anesthesia, intensive care unit management, and pain treatment . Recent in vitro and in vivo studies indicated that DEX has anti‐inflammatory activity and exerts potential protective effects against I/R‐induced skeletal muscle injury, and even remote organs like the lungs .…”
Section: Introductionmentioning
confidence: 99%
“…These studies were published between 2003 and 2019 and included a total of 1184 patients that underwent heart valve surgery or CABG. Of note, most of the RCTs were carried out in the USA and China (3 studies respectively), and the smallest trial included only 25 patients for each arm [27].…”
Section: Resultsmentioning
confidence: 99%